Design and Compared of Two Types of Microwave Moisture Instruments - Xibin Bu; Zelun Li (Institute of Advanced Engineering and Science, 2013)
In this paper, two types of microwave moisture measurement instruments were designed and compared with microwave dryness method and attenuation method separately. Compared with traditional moisture measurement instruments, the moisture instrument with microwave dryness method can detected the moisture content rapidly with high precision. On the other hand, the moisture instrument with microwave attenuation method can detect the moisture content with much higher speed but low precision, which can be used in the online measurement system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3073